Development of Canva-Based Interactive E-Module to Improve Students' Ability to Write Argumentation - Yusmaini Yusmaini; Edi Saputra (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Writing is one of the essential language skills that enables students to express ideas, knowledge, opinions, and experiences in writing. Besides serving as a means of communication, writing also develops students’ critical thinking and ability to organize ideas logically. However, many students at SMPN 2 Sinunukan still experience difficulties in writing argumentative texts due to limited vocabulary, inadequate understanding of text structure, low motivation, and the lack of interactive learning media. Therefore, the development of innovative instructional media is necessary to improve students’ argumentative writing skills. This study aimed to determine the practicality and effectiveness of the developed E-Module for teaching argumentative writing. The research was conducted at SMPN 2 Sinunukan with seventh-grade students as the research participants. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through classroom observations, interviews with Indonesian language teachers, validation questionnaires completed by media, material, and language experts, teacher and student response questionnaires to evaluate the practicality of the E-Module, and pre-test and post-test instruments to measure its effectiveness. The results of this study are expected to show that the developed E-Module is a valid, practical, and effective learning medium that can improve students’ argumentative writing skills and support a more engaging learning process.